Dongeng sebagai Desain Bahan Ajar Kreatif Bagi Anak Usia Dini (AUD) untuk Mengembangkan Kecerdasan Jamak (Multiple Intelligences) - Endah Kusumaningrum (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2016)
Abstract: Education at schools are often more concerned with the cognitive aspect. Teachers, parents, and society in general in still view that intellegence is limited academic skills (logical-mathematical). There’s paradigm that the smart kid is who get high scores and rank top in the class. The paradigm is too narrow if reviewed at the other intellegences in the nature of human beings. Howard Gardner says that man has eight intelligences that can be developed well through approriate direction (learning). There are linguistic, logical-mathematical, spatial, kinesthetic, musical, interpersonal, intrapersonal, and naturalist intellegence.Summarizes the various aspects required in the process of development of intellegence such as language (linguistic), the storyline (the logic of the story), social sensitivity (interpersonal and intrapersonal), conflict (the rhythm), imagination (visual/spatial), movement (kinesthetic), and nature (naturalist). Teachers can pack the teaching materials to be attractive to the fairy tale, that is expected to be easily grasped by children, so that the potential intellegence of nature child can be optimally developed. Keyword: Story telling, creative teaching materials, plural intelligence.